2010
DOI: 10.1002/jbm.b.31673
|View full text |Cite
|
Sign up to set email alerts
|

Does stem preheating have a beneficial effect on PMMA bulk porosity in cemented THA?

Abstract: In cemented total hip arthroplasty (THA), porosity plays a major role in the fatigue failure of bone cement. Stem preheating procedure is known to reduce the stem/ cement interfacial porosity. In the literature, no information is available about the effect of such procedure on cement bulk porosity. This study helps to find out if stem preheating can have a beneficial effect on bulk porosity, thus enhancing long-term bone cement integrity. A simplified experimental model of a stem/cement/bone construct of a cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 83 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Higher stem temperatures have been found to decrease cement polymerization time and interfacial porosity but have potential disadvantages. Firstly, shifting cement porosity towards the cement pre‐heat bone interface may cause untoward long‐term clinical survival of the cemented stem because crack distribution has been confirmed to be associated with the cement–bone interface. Secondly, increasing the temperature during cement polymerization by pre‐heating the stem may cause thermal necrosis in the bone tissue in the femoral canal; however, previous experimental studies have found no difference in polymerization temperature between stem preparation at 23 °C and 44 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Higher stem temperatures have been found to decrease cement polymerization time and interfacial porosity but have potential disadvantages. Firstly, shifting cement porosity towards the cement pre‐heat bone interface may cause untoward long‐term clinical survival of the cemented stem because crack distribution has been confirmed to be associated with the cement–bone interface. Secondly, increasing the temperature during cement polymerization by pre‐heating the stem may cause thermal necrosis in the bone tissue in the femoral canal; however, previous experimental studies have found no difference in polymerization temperature between stem preparation at 23 °C and 44 °C.…”
Section: Discussionmentioning
confidence: 99%